Sistem Pendukung Keputusan Staf Karyawan Terbaik Pada Rumah Sakit dengan Menggunakan Metode WASPAS - Yohana Melisa Simbolon (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This research is motivated by the problems faced by Estomih Hospital, Medan City, which is a container strategy in forming a way to process data or news for elements of a decision support system in handling or evaluating about how to service a job for the best employee at the Estomihi Hospital, Medan City and how to apply the method (WASPAS) in the sense of the word Weighted Aggregated Sum Product Assessment for making decisions to assess the best employee performance. To overcome the problem of evaluating employee performance processes at Estomihi Hospital, Medan City, it can be solved using the WASPAS method. Research was conducted to identify the best employees. This can be an accurate data in the selection of the best employees because it is categorized as one of the right ways for government agencies to evaluate employee performance. So as to produce a more stable and stronger value, therefore it is also necessary to update a system or designer in order to determine the maximum value of criteria and weight, the advantage of this method is that it is very easy and fast to overcome therefore this stage can be carried out so that it is easy to compare the criteria for very good employees or Top Telelent in such a way that employees who are rewarded attract the interest of managers. The calculation results show that the recipient of the award is ranked 1 by A5 on behalf of Bawardi Nimas with a score of 843,750. The advantage of the results of this study is the application of the best employee performance design because research uses the stages of designing a system which is said to be the WASPAS method, therefore the results provide an effective and efficient evaluation and facilitate management in evaluating employee performance, and exceeding expectations from. Indeed, employee performance appraisal can increase employee motivation to improve the quality of their performance